2011
DOI: 10.1007/s10886-011-9988-2
|View full text |Cite
|
Sign up to set email alerts
|

The Allelochemical L-DOPA Increases Melanin Production and Reduces Reactive Oxygen Species in Soybean Roots

Abstract: The non-protein amino acid, L-3,4-dihydroxyphenylalanine (L-DOPA), is the main allelochemical released from the roots of velvetbean and affects seed germination and root growth of several plant species. In the work presented here, we evaluated, in soybean roots, the effects of L-DOPA on the following: polyphenol oxidase (PPO), superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) activities; superoxide anion (O·-2), hydrogen peroxide (H(2)O(2)), and melanin contents; and lipid peroxidation. To this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…Increases in PPO activity and decreases in lipid peroxidation were observed in cucumber plants exposed to L-DOPA, 36 results also noted by Soares et al 37 in soybean roots. The reduction in lipid peroxidation may be related to the activity of antioxidant enzymes and/or suppression of ROS generation by quinoprotein formation.…”
Section: Effects Of L-dopa In Plantssupporting
confidence: 76%
See 3 more Smart Citations
“…Increases in PPO activity and decreases in lipid peroxidation were observed in cucumber plants exposed to L-DOPA, 36 results also noted by Soares et al 37 in soybean roots. The reduction in lipid peroxidation may be related to the activity of antioxidant enzymes and/or suppression of ROS generation by quinoprotein formation.…”
Section: Effects Of L-dopa In Plantssupporting
confidence: 76%
“…Furthermore, the application of an exogenous antioxidant agent (ascorbic acid) decreased PPO activity and lipid peroxidation, and reversed the growth-inhibition caused by L-DOPA in lettuce. 45 In this context, Soares et al 37 reported that L-DOPA (0.1-1.0 mM) increased PPO activity and melanin synthesis (roots become black) in soybean. The results showed that the increase in the PPO activity was associated with the browning root, suggesting that melanin synthesis came from the oxidation of L-DOPA.…”
Section: L-dopa: Pro-oxidant or Antioxidant?mentioning
confidence: 99%
See 2 more Smart Citations
“…In lettuce, L-DOPA (0.1 and 1 mM) doubled the PPO activity (Mushtaq et al, 2013a). Plants of Cucumis sativus and Glycine max presented inhibition of root growth and increased PPO activity after addition of L-DOPA (Soares et al, 2011;Mushtaq et al, 2013b). In lettuce, L-DOPA (1 mM) increased about 4 times the production of O -2 and H2O2 compared to untreated control.…”
Section: L-dopamentioning
confidence: 94%